Металічная сякера як паказнік абменных сувязяў Падзвіння ў эпоху бронзы - Лебедзь, В. А.; Lebedz, V. (Полоцкий государственный университет, 2021)
АРХЕАЛОГІЯ І ФІЗІЧНАЯ АНТРАПАЛОГІЯ ПАЎНОЧНАЙ БЕЛАРУСІ І СУМЕЖНЫХ ТЭРЫТОРЫЙ У ЕЎРАПЕЙСКІМ КАНТЭКСЦЕ На левобережье Западной Двины у деревни Залесье Полоцкого района Витебской области найден бронзовый топор с закраинами. В июле 2017 он поступил в Полоцкий краеведческий музей. Основные морфологические черты топора – это его форма: прямая обушковая и округло-трапецевидная рабочая части, закраины с ввогнутостью внутрь, плоская основа топора. Отличается от других типов топоров с закраинами формой закраин и формой нижней половины. Определяются также схожие черты с топорами с закраинами 1–3 ПЭБ2, с уступчатыми топорами 2–3 ПЭБ и с топорами с крыльями 3–1 половины 4 ПЭБ. Вероятно, что топор с закраинами с Залесья был изготовлен в те времена, когда в Европе уже использовались топоры с крыльями. Поэтому предварительно топор с Залесья можно датировать 3 – началом 4 ПЭБ (1300–1000 гг.до н.э.). Водный путь проникновения подобных топоров прослеживается с Восточной Прибалтики по реке Западная Двина.=A bronze ax with flanges was found on the left-bank region of the Western Dvina, near the village of Zalesse, Polatsk District, Vitsebsk Region. It was transferred to the Polatsk Museum of Local Lore in July 2017 The main morphological features of the ax are its shape: straight butt end and rounded trapezoidal working parts, flanges with a concavity inward, flat base of the ax. It differs from other types of flanged axes in the shape of the flanges and the shape of the lower part. Similar features are also identified with axes with flanges of the Bronze Age Periods 1–3, with stop-ridged axes of the Bronze Age Periods 2–3 and with axes with wings of the Bronze Age Periods 3– the first half of 4. It is likely that the flanked ax from Zalesse was made at a time when axes with wings were already used in Europe. Therefore, the ax from Zalesse can be preliminarily dated back to time of the Bronze Age Periods 3 – the first half of 4 (1300–1000 BC). The waterway of penetration of such axes can be traced from the Eastern Baltic region ...